Development of reduced reaction kinetics and fuel physical properties models for in-cylinder simulation of biodiesel combustion - Cheng, Xinwei (2016)
The analyses of spray, combustion and emission characteristics for two types of biodiesel fuels, namely coconut methyl ester (CME) and soybean methyl ester (SME) are reported in this thesis. In order to produce high fidelity numerical spray and combustion representation for CME and SME, accurately developed thermo-physical properties and chemical kinetics were integrated with open-source computational fluid dynamics codes. First, the thermo-physical properties of CME and SME which include liquid and vapour properties were calculated using temperature-dependent correlations that were found in the literature. These calculated thermo-physical properties were then incorporated into Open Field Operation and Manipulation (OpenFOAM) to determine the sensitivities of the fuel properties on the spray development. Based on the sensitivity analyses, 5 of 12 thermo-physical properties, including latent heat of vaporisation, liquid density, liquid heat capacity, liquid surface tension and vapour pressure, gave the largest fluctuation to the spray development. Besides, coupled effects among the thermo-physical properties were discovered. The effects of thermo-physical properties were also varied according to the addition of unsaturation levels and combustion chemistries.